2006
DOI: 10.1111/j.1528-1167.2006.00573.x
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Significance of Gap Junction Channels in the Epileptogenicity and Seizure Susceptibility of Juvenile Rats

Abstract: Summary: Purpose:The functional significance of gapjunction (GJ) channels in seizure susceptibility and induction and maintenance of seizures in the developing rat brain was investigated on the 4-aminopyridine (4-AP) in vivo epilepsy model. Methods:In electrophysiological experiments, GJs were manipulated with a blocker or opener before induction or at the active epileptic foci between postnatal days 9 and 28 (P9-28). Semiquantitative reverse transcriptase-polymerase chain reaction (RT-PCR) amplification was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 46 publications
1
31
0
1
Order By: Relevance
“…Recently there has been increased interest in the role of gap junctional intercellular communication in modulating this synchronized activity (Gajda, et al 2006, Traub, et al 2004). …”
Section: Introductionmentioning
confidence: 99%
“…Recently there has been increased interest in the role of gap junctional intercellular communication in modulating this synchronized activity (Gajda, et al 2006, Traub, et al 2004). …”
Section: Introductionmentioning
confidence: 99%
“…Gajda and colleagues reported that, in anaesthetized adult rats, seizure amplitude and duration was reduced by the non-specific gap junction blocker carbenoxolone and potentiated by the gap junction opener trimethylamine after seizure induction with 4-aminopyridine [49]. They proposed that the increased epileptogenicity of the developing brain compared to adult brains is mediated by enhanced gap junction communication [48]. Interestingly when trimethylamine was applied 60 minutes after 4-aminopyri dine in postnatal rats, discrete seizures were replaced with periods of status epilepticus [48].…”
Section: Connexins In the Brainmentioning
confidence: 96%
“…In epilepsy a number of connexins have been shown to be upregulated including Cx26, Cx36 and Cx43 in rats, and Cx43 in human post mortem brain tissue [39,48]. The role of gap junctions in the propagation of seizures has been extensively investigated.…”
Section: Connexins In the Brainmentioning
confidence: 99%
“…As descobertas deste estudo sugerem que as JC não estão apenas envolvidas na gênese rítmica e na sincronização da atividade cortical, mas também podem ser responsáveis pela elevada epileptogenicidade do cérebro em desenvolvimento. 13 Szente e cols. (2002) investigaram o papel das JC na indução e manifestação de crises induzidas por 4-AP no neocórtex de ratos.…”
Section: Figura 1 Junções Comunicantesunclassified